Managerial Performance Study: The Role Of Budget Participation And Budget Clarity With Accounting Information System Characteristics As Moderating Variables - Irfan, Irfan (International Journal Of Economics Social And Technology (IJEST), 2025)
This study uses a quantitative approach. The population in this study consisted of 131 people, the sample in this study was 131 respondents. This study uses the Partial Least Square methodology. Processing data and drawing conclusions, researchers use the SmartPLS program. Based on the results of the study Budget participation affects managerial performance at PT. North Sumatra Plantation, clarity of budget targets affects managerial performance at PT. North Sumatra Plantation. The characteristics of the management accounting information system that acts as a moderating variable are stated to be able to moderate the relationship between budget participation and managerial performance which has been tested through the absolute difference test. The characteristics of the management accounting information system that acts as a moderating variable are stated to be able to moderate the relationship between clarity of budget targets and managerial performance which has been tested through the absolute difference test